A Flipped Classroom Case to Introduce OB/GYN Clerkship Students to Contraception, Postpartum Care, and Intimate Partner Violence Screening - Krista Wagoner; Angela Dempsey; Faith Dunn; Meredith Chardukian (MedEdPORTAL)
Introduction The Association of Professors of Gynecology and Obstetrics core learning objectives for medical students include postpartum care, peripartum mood disorders, family planning, and intimate partner violence. Methods This module uses student prework, session slides, and a facilitator guide for a 2-hour flipped classroom case that addresses these core learning areas for medical students on their obstetrics and gynecology clerkship. We assessed the module in a range of domains with five rotations of students who participated during their clerkship and facilitators who led the session. Data were collected from students and facilitators via voluntary participation in a survey made available after the session. Data are reported as proportion of respondents who agreed or strongly agreed. Results Of 97 student participants, 57 completed the survey (59%). More than 85% agreed or strongly agreed that the session improved understanding or comfort in each of the learning objectives, and the majority agreed that the prework offered useful knowledge for the session (89%), that the session was interactive (91%), and that the session format was helpful in applying new knowledge (95%). Fifty-seven percent of facilitators responded; all agreed that the facilitator guide increased their confidence while teaching and that they spent less time preparing for the session than traditional didactics. Most (89%) agreed that the facilitator guide helped them promote active learning. Discussion With favorable student and facilitator perceptions, this module provides a tool to address several core learning objectives for medical students in the context of an interactive flipped classroom module.